Captura y almacenamiento de carbono en sistemas agroforestales instalados en el Instituto Nacional de Investigación Agraria (INIA). Región Loreto - Tuesta Villacorta, Isaac (2013)
The purpose of this research was to determine the values of efficient carbon capture and storage in agroforestry systems implemented at INIA (Iquitos-Nauta highway), and to know their sustainable management. The research is descriptive and qualitative, analyzing the characteristics of the carbon sequestration potential of the species within the system. The evaluation of carbon fixation was carried out following the methodology indicated in the Sampling Protocols for Biomass and Carbon in Alternative Projects to slash and burn. As a final result, when evaluating a hectare of agroforestry systems implemented since 1996-1997, encouraging results of capturing carbon from 16,299 MT/has to 49,964 MT/has are obtained. The plot that obtained the highest carbon capture, species of tornillo, soursop, sangre de grado, caspi lizard are observed where species with DAP greater than 50 cm are observed, as in the case of tornillo (60.0 cm.), lizard caspi (50.0 cm.), soursop (? 80 cm.), sangre de grado (59.0 cm.). According to bibliographic data, it is reported that an agroforestry plot can produce 24.1 MT/Ha., in 9 years (for 13 years it will be 34.81 MT/ha.) and observing the results obtained, plots 4 to 7 show homogeneity in terms of to the growth of their species because they are close to the established range (they capture carbon in ranges from 35.16 to 49.96 MT/Ha). The continuous growth of the species plus the production of fruit trees and the possible adoption of this technology can generate great economic income. On average, in the lower range, there are 16.22 MT/ha of C, with sales prices: 324.4 dollars/ha. By reforesting quantities of degraded areas and exchanging conservation of resources for carbon credits, necessary profits are obtained to develop other productive projects with a sustainability character, under the premise of conserving production.